Testing the effects of prey surface changes on Bdellovibrio bacteriovorus predation - Lai, Ting (2019)
Bdellovibrio bacteriovorus is an invasive bacterial predator of a wide range of Gram negative bacteria including many ESKAPE pathogens. It attaches to the outer membrane of the prey cell and invades into the periplasm of prey cells, ultimately killing the cell from the inside. The target for prey recognition on the outer membrane is currently unknown. B. bacteriovorus is predatory both in vitro and in vivo in zebrafish for several of these pathogens. However, some pathogens are known to adapt their membrane composition when stressed by host or other different environments. One such pathogen is Acinetobacter baumannii.